Enhanced glaucomatous damage accompanied by glial response in a new multifactorial mouse model - Reinehr, Sabrina; Girbig, Renée M.; Schulte, Kim K.; Theile, Janine; Asaad, M. Ali; Fuchshofer, Rudolf; Dick, H. Burkhard; Joachim, Stephanie C. (Frontiers in Immunology, 2023)
Glaucoma is a complex, multifactorial neurodegenerative disease, which can lead to blindness when untreated. It seems that, among others, immune processes, elevated intraocular pressure (IOP), or a combination of these factors are responsible for glaucomatous damage. Here, we combined two glaucoma models to examine if a combination of risk factors (IOP and immune response) results in a more severe damage of retinal ganglion cells (RGCs) and the optic nerves as well as an additional glia activation. Hence, six-week-old wildtype (WT+ONA) and βB1-CTGF mice (CTGF+ONA) were immunized with 1 mg ONA (optic nerve antigen). A wildtype (WT) and a βB1-CTGF control group (CTGF) received sodium chloride instead. IOP was measured before, and every two weeks after immunization. After 6 weeks, electroretinogram (ERG) measurements were performed. Then, retinae and optic nerves were processed for (immuno-) histology. Further, mRNA levels of corresponding genes in optic nerve and retina were analyzed via RT-qPCR. 6 weeks after immunization, the IOP in CTGF and CTGF+ONA mice was increased. The optic nerve of CTGF+ONA animals displayed the most severe cell inflammation, demyelination, and macroglia activation. Fewer numbers of oligodendrocytes were only observed in WT+ONA optic nerves, while more apoptotic cells triggered by the extrinsic pathway could be revealed in all three glaucoma groups. The number of microglia/macrophages was not altered within the optic nerves of all groups. The loss of neuronal cells, especially RGCs was most pronounced in CTGF+ONA retinae in the central part and this was accompanied by an enhanced activation of microglia/macrophages. Also, Müller cell activation could be noted in CTGF and CTGF+ONA retinae. In the new model, an additive degeneration could be noted in optic nerves as well as in the number of RGCs. These results suggest a potential additive role of high IOP and immune factors in glaucoma development, which will aid for understanding this multifactorial disease more precisely in the future.